Reconstructing the Vocational Education Ecosystem within the Framework of the Golden Indonesia Vision 2045: Human Capital Gap Analysis and Acceleration Strategy - Hertanto, Yudhi (International Journal of Asian Education, 2025)
This study evaluates the readiness of the vocational education (SMK) ecosystem in Indonesia towards the Human Capital Index and labor productivity targets in the 2025-2045 National Long-Term Development Plan (RPJPN) towards the Golden Indonesia Vision 2045. The study aims to analyze performance gaps, identify structural barriers, and formulate acceleration strategies. Using a descriptive qualitative approach with a systematic literature review (SLR) and secondary data analysis (2023-2025), the population includes policy documents, BPS statistics, and SINTA/Scopus indexed articles (n>500), purposively sampled into 45 articles and 12 primary documents. The PRISMA-based SLR protocol and Miles-Huberman-Saldana interactive analysis ensure validity through macro-micro triangulation. The results show crucial gaps: TPT of SMK graduates is 8.62% versus the target of 3-4%, low HCI (0.54), persistent skills mismatch, teacher competency deficits violating Prosser's postulate, and Teaching Factory is not market-oriented. In conclusion, ecosystem reconstruction requires revitalization of BLUD, teacher returnship, and integration of green-digital curriculum to realize the demographic dividend..